2005
DOI: 10.1158/1078-0432.ccr-04-2421
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Molecular Subtypes Respond Differently to Preoperative Chemotherapy

Abstract: Purpose: Molecular classification of breast cancer has been proposed based on gene expression profiles of human tumors. Luminal, basal-like, normal-like, and erbB2+ subgroups were identified and were shown to have different prognoses. The goal of this research was to determine if these different molecular subtypes of breast cancer also respond differently to preoperative chemotherapy. Experimental Design: Fine needle aspirations of 82 breast cancers were obtained before starting preoperative paclitaxel followe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

70
1,068
7
80

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,639 publications
(1,245 citation statements)
references
References 17 publications
70
1,068
7
80
Order By: Relevance
“…Luminal A cancers are usually of low histological grade, Table 3 The results of an analysis to identify genes whose expression is correlated with copy number: correlation between expression values and smoothed aCGH log2 ratios strong ERa expressers and rarely metastasise, whereas breast cancer cell lines harbour genomic features consistent with high histological grade (e.g., gains of 1q, 8q and 20q) [31], are usually derived from ERa negative samples and metastatic deposits [4]. Normal breast-like has been shown to be an unstable subgroup and there is evidence to suggest that samples pertaining to this subgroup are enriched for stromal cells [46,47]. Second, although numerous genetic changes are prevalent in all subgroups of breast cancer cell lines (e.g., gains of 1q, 8q and 20q), each subgroup seems to be characterised by a rather specific constellation of genetic changes (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Luminal A cancers are usually of low histological grade, Table 3 The results of an analysis to identify genes whose expression is correlated with copy number: correlation between expression values and smoothed aCGH log2 ratios strong ERa expressers and rarely metastasise, whereas breast cancer cell lines harbour genomic features consistent with high histological grade (e.g., gains of 1q, 8q and 20q) [31], are usually derived from ERa negative samples and metastatic deposits [4]. Normal breast-like has been shown to be an unstable subgroup and there is evidence to suggest that samples pertaining to this subgroup are enriched for stromal cells [46,47]. Second, although numerous genetic changes are prevalent in all subgroups of breast cancer cell lines (e.g., gains of 1q, 8q and 20q), each subgroup seems to be characterised by a rather specific constellation of genetic changes (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic expression profiling studies have identified distinct subtypes of breast carcinomas that are associated with different responses to chemotherapy and to different clinical outcomes in the preoperative setting [24]. Luminal types A, B, C, normal breast, HER2-positive, and basallike phenotypes have been reproducibly separated [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…The absence of weak intensity and ambiguous background staining made positive reactions very distinct. We used a molecular classification schema for breast cancers as reported 13,[16][17][18][19] to class those that were positive for MGB1. Basal cell-like subtypes were significantly less frequent among breast cancers that expressed MGB1 (w 2 test, P ¼ 0.01).…”
Section: Mgb1 Expression and Breast Cancer Subtypementioning
confidence: 99%